Power decoupling strategy based on ‘virtual negative resistor’ for inverters in low-voltage microgrids - Zhang, Ping; Zhao, Hengyang; Cai, Huanyu; Shi, Jianjiang; He, Xiangning (IET power electronics, 2016)
In a low-voltage microgrid, due to the effect of mainly resistive line impedance, the conventional P/w and Q/E droop control is subject to the coupling and dynamic instability of the real and reactive power control. To address this problem, a novel virtual impedance composed of virtual negative resistor (VNR) and virtual inductor is employed to control the interfaced inverters in this study. The virtual resistance is controlled to be negative to counteract the effect of the line resistance thus ensuring a mainly inductive system impedance. However, it is found in this study that, the grid-connected inverter system may present non-fundamental instability if the line resistance drifts to be smaller than the value of VNR with the basic VNR method. To produce a more stable system when the line parameter drifts, an improved VNR form based on a proportional-resonant structure is proposed. Moreover, an interesting conclusion is obtained that, if the PI voltage regulator and the basic VNR are used, the grid-connected inverter becomes critical stable when the virtual resistance is exactly equal to the line resistance. Experimental results of a low-voltage microgrid consisting of two 6-kW inverters are given to validate the control strategy.